Colonialism, malaria, and the decolonization of global health - Jesse B. Bump; Ifeyinwa Aniebo (Public Library of Science (PLoS), 2022)
This paper explores the decolonization of global health through a focus on malaria and European colonialism in Africa. We employ an historical perspective to better articulate what "colonial" means and to specify in greater detail how colonial ideas, patterns, and practices remain an obstacle to progress in global health now. This paper presents a history of malaria, a defining aspect of the colonial project. Through detailed analysis of the past, we recount how malaria became a colonial problem, how malaria control rose to prominence as a colonial activity, and how interest in malaria was harnessed to create the first schools of tropical medicine and the academic specialization now known as global health. We discuss how these historical experiences shape malaria policy around the world today. The objective of this paper is to advance discussion about how malaria and other aspects of global health could be decolonized, and to suggest directions for future analysis that can lead to concrete steps for action.